Analysis of Gyaku Tsuki's Punch Motion on Junior Class Karate Athletes at Dojo Surya Yudha Prestasi - Arbin Ranggaseta Dwiantika; Fajar Awang Irawan (Journal Of Sport Education (JOPE), 2024)
The purpose of this study was to analyze the motion of the Gyaku Tsuki on Junior Class Karate athletes at Dojo Surya Yudha Prestasi. This type of research uses quantitative research with survey methods. The sample in this study were junior class athletes at Dojo Surya Yudha Prestasi, Banjarnegara Regency (16- 17 years old), totaling 11 athletes. Data analysis techniques in this study used the Kinovea 0.9.5 application. Analysis of the punching movement of Gyaku Tsuki athlete Dojo Surya Yudha Prestasi has an average speed of 0.58 seconds, an average distance between the feet of 84.3 cm, an average punch speed of 16.4 meters/s, an average right arm angle when hitting is 172.1 degrees, the average striking angle is 152.8 degrees, the average left leg angle is 109.9 degrees, and the average right leg angle is 120.7 degrees. The conclusion found that the angle of the right arm, the angle of the left leg, the angle of the right leg, and the angle of the strike formed greatly influence the speed of Gyaku Tsuki's punch. So good coordination and correct technique are needed to optimize the Gyaku Tsuki punch movement. It is hoped that further research can discuss the effectiveness of Gyaku Tsuki's punch.